2018
DOI: 10.1021/acs.est.7b04397
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Transformations and Algal Toxicity of Single-Layer Molybdenum Disulfide Regulated by Humic Acid

Abstract: The environmental transformations of nanomaterials are correlated with their behaviors and ecological risks. The applications of single-layer molybdenum disulfide (SLMoS) have rapidly developed in environmental fields, but the potential transformations and biological effects of SLMoS remain largely unknown. This study revealed that humic acid (HA, over 10 mg/L) induced the scrolling of SLMoS with light irradiation over a 56-day incubation. The colloidal stability of SLMoS increased, and the aggregation ratio d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 58 publications
6
49
0
Order By: Relevance
“…In a more recent study, Zou et al explored the environmental transformation of MoS 2 after exposure to humic acid in an aqueous environment. 170 The chemical dissolution of MoS 2 increased significantly upon exposure to humic acid, and the resulting humic acid−MoS 2 complex showed higher peroxidase-like catalytic activity. In order to better assess their ecological and biological risks, further study is required to understand the environmental transformations of 2D materials, which will in turn affect their biological interactions and outcomes.…”
Section: D Materials Hazard Assessmentmentioning
confidence: 98%
See 1 more Smart Citation
“…In a more recent study, Zou et al explored the environmental transformation of MoS 2 after exposure to humic acid in an aqueous environment. 170 The chemical dissolution of MoS 2 increased significantly upon exposure to humic acid, and the resulting humic acid−MoS 2 complex showed higher peroxidase-like catalytic activity. In order to better assess their ecological and biological risks, further study is required to understand the environmental transformations of 2D materials, which will in turn affect their biological interactions and outcomes.…”
Section: D Materials Hazard Assessmentmentioning
confidence: 98%
“…While the Pluronic-dispersed MoS 2 demonstrated high dispersion stability in aqueous solution, the material was more likely to bind irreversibly to the quartz porous media than the chemically exfoliated MoS 2 , which was highly mobile in the sand columns. In a more recent study, Zou et al explored the environmental transformation of MoS 2 after exposure to humic acid in an aqueous environment . The chemical dissolution of MoS 2 increased significantly upon exposure to humic acid, and the resulting humic acid–MoS 2 complex showed higher peroxidase-like catalytic activity.…”
Section: D Materials Hazard Assessmentmentioning
confidence: 99%
“…Once exposed to natural environments, nanomaterials would inevitably interact with natural organic matter (NOM), which is abundant in natural soils and ground waters with the range of a few mg/L to a few hundred mg/L. It has been reported that NOM could affect the physicochemical properties and biological activities of nanomaterials. For example, the stability of nanomaterials could be enhanced in the presence of NOM through electrostatic repulsion or steric hindrance. , The nanomaterials coated with NOM showed minor toxicity to bacteria through shielding reactive sites …”
mentioning
confidence: 99%
“…67,68 However, a recent study reported that the covalent hybridization of humic acid with single-layered MoS 2 (with a predominantly 1T phase) occurs through the S atoms. 69 Increased adsorption of humic acid at lower pH has previously been shown for both clay minerals via the interaction of aliphatic and aromatic moieties 70,71 with hydroxyl groups at the positively charged sites of the clays; these interactions are driven by electrostatic interactions and ligand exchange. 72 As pH is increased, however, electrostatic repulsions between NOM and clays reduce, and the interaction begins to be driven primarily by hydrophobic or H-bonding interactions.…”
Section: ■ Results and Discussionmentioning
confidence: 96%